Selected works of Oscar Wilde - Wilde, Oscar (New Delhi : Jainco publishers)
These volumes represent each author's best and most famous writings. This finely crafted and affordable series offers the works of these world-renowned authors to a wider audience. Includes The Importance of Being Earnest, The Picture of Dorian Gray, and others.
Keywords: English literature; English fiction; Literature anglesite